Analisa Perhitungan Solusi Cerdas Terhadap Perkembangan Teknologi Informasi & Komunikasi (TIK) Pada Sistem Bunga Tabungan Perbankan Global via Sistem Bunga Metris dan Metris Plus - Stephanus Ivan Goenawan (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
This paper describes the smart solution of the negative effects of Information & Comunication Technology (ICT) developments to the current system of bank interest. The weaknesses of the current bank interest rate system can be fixed by the Metris Plus and Metris interest system so it can’t cause the negative effects to the bank or the customer